Endothelial soluble epoxide hydrolase links polyunsaturated fatty acid metabolism to oxidative stress and atherosclerosis progression - Cao, Minghua; Li, Mengqing; Li, Xixuan; Li, Yuanyuan; Chen, Yunyun; Drekolia, Maria-Kyriaki; Cheng, Xiang; Delgado Lagos, Fredy Andrés; Bibli, Sofia-Iris; Hu, Jiong (Redox Biology, 2025)
Atheroslcerosis manifests as localized lesions within the vascular tree, preferentially affecting arteries at branch points, the outer wall of bifurcations and the inner walls of curvatures. Such spatial localized sensitivity to atherosclerosis, can be partially attributed to endothelial cell heterogeneity which compromises vascular fitness and contributes to the pathogenesis of the diseases. Here we identified that in a subcluster of aortic endothelial cells characterized with atheroprone gene signatures, the polyunsaturated fatty acids (PUFAs) metabolic enzyme soluble epoxide hydrolase (sEH) is selectively upregulated. Genetic endothelial-specific overexpression of the sEH resulted in excessive and accelerated atherosclerosis development, while inducible endothelial-specific deletion of sEH protected against PCSK9 mediated atherosclerotic plaque formation. Mechanistically, sEH-derived docosahexaenoic acid (DHA) diol (19,20-DHDP) disrupts mitochondrial protein-cholesterol associations in endothelial cells, which through reduced oxidizing metabolic import of pyruvate and malate inhibited mitochondrial Complex I activity. Such inhibition, resulted in a lowering of the mitochondrial membrane potential and subsequent excessive mitochondrial reactive oxygen species production and disrupted mitochondrial structure. Heightened mitochondrial redox generation ultimately led to TGFβ activation and the subsequent stimulation of an athroprone and pro-inflammatory endothelial transcriptional programme. Re-establishing redox homeostasis by antioxidant treatments, halted the atheroprone phenotypes of sEH overexpressing vessels. Our data propose that manipulating endothelial PUFA metabolism and sEH activity in the endothelium can exert vascular protective effects.
Online verfügbar: 14. Juni 2025, Artikelversion: 18. Juni 2025
Gesehen am 25.09.2025